Analysis of the Effect of Shaft Angle on Dynamic Characteristic of the Split Torque Transmission System with Herringbone gear - Cao Jianfeng; Chen Zhigang; Chen Siyu; Tang Jinyuan (Jixie chuandong)
The effects of shaft angles,which define the locations of gear centers,on dynamic characteristics of a split torque transmission system with herringbone gears are investigated. Firstly,the shaft angles are derived based on adjacency relationship,concentric relationship,geometrical conditions and installation conditions. Then,the dynamics model of the motion of the system which consists of shafts,bearings,gear rotors and the process of gear mesh is established based on the finite element node modeling method. Finally,the dynamic response of the system is calculated based on rotor dynamics theory,and the dynamic load coefficients and dynamic transmission error are obtained under different shaft angles so as to indicate the effects of shaft angles on the dynamic characteristics. The research shows that shaft angles have a great influence on the dynamic characteristics of the system,when the shaft angle is different,the frequency domain distribution of system dynamic response is very different,at different speeds,the shaft angle has different influence on the dynamic load coefficient and dynamic response.